Health-related quality of life in primary hepatic cancer: a systematic review assessing the methodological properties of instruments and a meta-analysis comparing treatment strategies - Wohlleber, Kerstin; Heger, Patrick; Probst, Pascal; Engel, Christoph; Diener, Markus K.; Mihaljevic, André Leopold (Quality of life research, 2021)
Patient-reported outcomes including health-related quality of life (HRQoL) are important oncological outcome measures. The validation of HRQoL instruments for patients with hepatocellular and cholangiocellular carcinoma is lacking. Furthermore, studies comparing different treatment options in respect to HRQoL are sparse. The objective of the systematic review and meta-analysis was, therefore, to identify all available HRQoL tools regarding primary liver cancer, to assess the methodological quality of these HRQoL instruments and to compare surgical, interventional and medical treatments with regard to HRQoL.